DETERMINAN FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN PERBANKAN DI INDONESIA DENGAN MENGGUNAKAN FRAUD PENTAGON THEORY - Ripa Fajarina Laming; Adil Setiawan; Nita Kartini (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
Fraudulent financial reporting is one of the most common types of fraud that occurs in Indonesia. This study looks at the determinants of fraud using the latest fraud theory, namely fraud pentagon theory. This study aims to analyze the effect of pressure, opportunity, rationalization, competence, and arrogance simultaneously on fraudulent financial reporting. The sampling technique in this study using purposive sampling. A sample of 26 banking companies listed on the Indonesia Stock Exchange (IDX) within 10 years. The research data uses the company's annual report for the period 2009-2018 obtained from the Indonesia Stock Exchange (IDX). The analysis method used is multiple linear regression using SPSS version 24. The results show that pressure, opportunity, rationalization, competence, and arrogance simultaneously have a positive and significant effect on fraudulent financial reporting.